Representasi Minangkabau Tabedo dalam Novel-Novel Pengarang Minangkabau Sesudah PRRI - Ronidin, Ronidin; Sudibyo, Sudibyo; Indrastuti, Novi Siti Kussuji (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This article is about the representation of Minangkabau tabedo in the novels of Minangkabau authors after PRRI (Pemerintahan Revolusioner Republik Indonesia). Minangkabau tabedo is a manifestation of the difficult and dilemmatic socio-ideological conditions faced by the Minangkabau people after PRRI. The data of this research are taken from the novels of Minangkabau authors after PRRI, namely Dari Puncak Bukit Talang by Soewardi Idris, Panggilan Tanah Kelahiran by Dt. B. Nurdin Jacub, Saraswati Si Gadis dalam Sunyi by A.A. Navis, Warisan by Chairul Harun, and Bako by Darman Moenir. The analysis of the novels is based on Lucien Goldmann's theory of genetic structuralism and its dialectical method, and is supported by Lotman's theory of narrative text regarding the elaboration of the structure of literary works as a conceptual construction centred on the idea of binary opposition. The findings of this article show that Minangkabau tabedo is a complex of ideas and worldviews of the author that are homologously expressed in the structure of the novel and the social structure of post-PRRI Minangkabau society. The representation of Minangkabau tebedo is seen through the changes taking place in Minangkabau society, such as the shift in Minangkabau family identity from matrilineal to patrilineal; changes in the behaviour of overseas Minangkabau who are uprooted from the roots of tradition, morality and religion; the diminishing role of traditional elites such as the mamak and alim ulama; the increasingly dominant role of fathers, eliminating the role of the mamak; the fading of communal culture and the development of individual lifestyles.